Comparison of Cytotoxicity of AH Plus and DC Canal SE Sealer After Final Setting - AA Moshari; E Esnaashari; S Eskandarion; B Safari (Islamic Azad University, 2022)
Background and Aim: This study aimed to compare the cytotoxicity of AH Plus and DC Canal SE sealer after final setting. Materials and Methods: In this in vitro, experimental study, human gingival fibroblasts (HGFs) were cultured in Dulbecco's modified Eagle's medium supplemented with 10% fetal bovine serum, 100 U/mL penicillin, and 100 µg/mL streptomycin, and incubated at 37°C and 5% CO2. Cells at a density of 5000 cells/well were seeded in a 96-well plate for the methyl thiazolyl tetrazolium (MTT) assay. The cells were incubated with AH Plus and DC Canal SE sealers. Specimens of freshly mixed sealers were fabricated with 4 mm height and 10 mm diameter, and  incubated at 37°C for 24 hours for setting. Each specimen was incubated with 10 mL of diluted culture medium at 37°C and 5% CO2 for 24 hours. Finally, the solution was filtered using a 0.22-µm filter. Different dilutions (1, 1/2, 1/4, 1/8) were prepared, and cell viability was assessed at 24 and 72 hours by measuring the optical density of the solutions spectrophotometrically. Data were analyzed by ANOVA and Tukey's test. Results: Cell viability in presence of all concentrations of AH Plus and DC Canal SE was significantly lower at 72 hours compared with 24 hours (P<0.001). Cell viability in presence of AH Plus was significantly higher compared with DC Canal SE at all concentrations and time points. Conclusion: Cell viability was higher in presence of AH Plus compared with DC Canal SE sealer in all concentrations and time points.